Research Trends and Collaboration Patterns on Polymyxin Resistance: A Bibliometric Analysis (2010–2019) - Quincho-Lopez, Alvaro; Pacheco-Mendoza, Josmel (Frontiers in Pharmacology, 2021)
Abstract Background: Antimicrobial resistance is a serious public health problem that has become a global threat. Special attention should be given to polymyxins (polymyxin B and colistin) which, since their reintroduction into clinical practice, are considered "last resort" drugs. The objective of this study is to perform a bibliometric analysis of scientific research on polymyxin resistance. Methods: Scopus was used to retrieve documents relevant to polymyxin resistance from 2010 to 2019. Data was exported to Microsoft Excel for table presentation. SciVal was used for volume and citation analysis as well as collaboration patterns. Also, we extracted data regarding the top documents, authors, countries, institutions, and the metrics of journals. VantagePoint and VOSviewer were used for geographical distribution of worldwide research and keyword co-occurrence analysis, respectively. Results: A total of 1409 documents were retrieved. The retrieved documents received 25.0 citations per document. Articles (73.88%) and letters (18.09%) were the most frequent types of documents. During 2010-2019, there was a significant growth in publications (p-value < 0.001). The received citations were 35,209 with a peak in 2016 (11,250 citations). China and the United States led the scientific production with 299 (21.2%) and 238 (16.9%) publications, respectively. Little or no contribution came from central Asia, Sub-Saharan Africa, and Latin America. Chinese institutions have caused the greatest impact, with University of Zhejiang (China) being the most prolific institution on the subject (88 documents). In terms of the most productive journals, Antimicrobial Agents and Chemotherapy ranked first with 196 (13.9%) documents. Most of the documents were published in quartile 1 journals and only had national collaboration (43.2%). Analysis of keyword co-occurrence revealed that research on polymyxin resistance during the last decade has focused on its relationship with public health, pharmacology, and genetics. Conclusion: The number of documents on polymyxin resistance has increased significantly in the recent years, with a steep growth from 2016 onwards. China and the United States led the scientific production. Most of the documents were published in high-quality journals. Greater joint efforts and more contribution from central Asia, Sub-Saharan Africa, and Latin America are still needed to tackle this global problem.